A kind of green lightweight wet-mixed mortar and preparation method thereof

By optimizing the green lightweight wet-mixed mortar formula and construction technology, the problems of traditional wet-mixed mortar are solved, and building materials with high strength, low thermal conductivity and high resource utilization are achieved, suitable for high-strength and energy-saving buildings.

CN119750975APending Publication Date: 2025-04-04GUANGDONG XINRUILONG ECOLOGICAL BUILDING MATERIALS CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411983398.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

Traditional wet-mixed mortars have problems such as large weight, insufficient environmental protection performance, high energy consumption, poor construction performance, insufficient durability and excessive dependence on natural resources. The construction process is complicated and it is difficult to effectively utilize recycled micro powder.

Method used

The composition and construction process of the mortar are optimized through ultrasonic dispersion, ball milling and precise water-cement ratio control.

Benefits of technology

It significantly improves compressive strength and crack resistance, reduces thermal conductivity, improves resource utilization, reduces environmental pollution, is suitable for high-strength and energy-saving building needs, and is suitable for crack-sensitive walls and decoration projects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119750975A_ABST
    Figure CN119750975A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of building materials, and provides a green lightweight wet-mixed mortar, comprising the following components in weight percentage: cement: 30%-35%; functional lightweight aggregate: 20%-26%; recycled micropowder: 10%-12%; self-healing microcapsule material: 0.5%-1.0%; polypropylene fiber: 0.5%-0.7%; modified mineral admixture: 5%-8%; surfactant: 0.2%-0.4%; water reducer: 0.3%-0.5%; water: 16.3%-27%; wherein the recycled micropowder is obtained by crushing, screening and grinding waste concrete and waste bricks to obtain fine powder with an average particle size controlled between 10 and 30 microns. The green lightweight wet-mix mortar of the present invention greatly improves the compressive strength through the active filling of recycled micropowder and the optimization of functional lightweight aggregate, meeting the needs of high-strength building applications. The introduction of self-healing microcapsule materials and polypropylene fibers significantly improves the mortar's crack resistance and flexural resistance, making it suitable for crack-sensitive walls and decoration projects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building materials, and in particular to a green lightweight wet-mix mortar and a preparation method thereof. Background Art

[0002] Wet-mixed mortar is widely used in construction projects due to its convenient construction and stable quality. However, traditional wet-mixed mortar generally has the problems of heavy weight, insufficient environmental protection performance and high energy consumption. Lightweight and green are important development directions in the field of mortar. Although there are some lightweight mortars in the existing technology, they generally have problems such as poor construction performance, low strength and insufficient durability.

[0003] For example, the Chinese patent CN111410502B discloses an anhydrite-based lightweight plaster mortar and its preparation method. Although the anhydrite after physical grinding is optimized and added with an activator to improve the hydration activity, and is mixed with cement and fly ash, and is equipped with vitrified microspheres and various admixtures, the reliability of strength during the construction process is ignored, resulting in a complex and difficult construction process. At the same time, the recycled micropowder cannot be used, and the resources cannot be fully utilized.

[0004] In addition, the prior art also has the following defects:

[0005] 1. A large amount of cement is used as a binder in traditional mortar, and the carbon emissions during the cement production process are high; the raw materials in mortar materials are mostly natural resources (such as sand, stone powder, etc.), and excessive exploitation causes damage to the environment.

[0006] 2. Traditional mortar is prone to cracks during the hardening process, affecting durability and service life. The workability and water retention of mortar are poor, especially in special construction environments such as high temperature and low humidity, it is prone to stratification and water seepage.

[0007] 3. Under long-term load, humidity and temperature changes, traditional mortar is prone to microcracks, resulting in a decrease in material strength.

[0008] The present invention is made in order to solve the common problems in the art such as heavy weight, lack of green and environmentally friendly materials, insufficient performance and poor durability. Summary of the invention

[0009] The purpose of the present invention is to propose a green lightweight wet-mix mortar and a preparation method thereof in view of the current deficiencies.

[0010] In order to overcome the shortcomings of the prior art, the present invention adopts the following technical solutions:

[0011] A green lightweight wet-mixed mortar, comprising the following components in percentage by weight:

[0012] Cement: 30%-35%;

[0013] Functionalized lightweight aggregate: 20% to 26%;

[0014] Recycled micro powder: 10% to 12%;

[0015] Self-healing microcapsule material: 0.5%~1.0%;

[0016] Polypropylene fiber: 0.5% to 0.7%;

[0017] Modified mineral admixture: 5% to 8%;

[0018] Surfactant: 0.2% to 0.4%;

[0019] Water reducing agent: 0.3%~0.5%;

[0020] Water: 16.3%~27%;

[0021] The regenerated micro powder is obtained by crushing, screening and grinding waste concrete and waste bricks to obtain fine powder with an average particle size controlled between 10 and 30 microns.

[0022] Optionally, the self-healing microcapsule material includes a shell layer and a core layer, the shell layer material is made of a high molecular polymer, and the core layer is calcium silicate slurry (CaO-SiO2-H2O) or epoxy resin.

[0023] Optionally, the functionalized lightweight aggregate includes surface-modified expanded perlite or floating beads.

[0024] Optionally, the modified mineral admixture includes silica fume or fly ash.

[0025] The present invention also provides a method for preparing a green lightweight wet-mixed mortar, which comprises the following steps:

[0026] S1. Prepare surfactant solution:

[0027] In a clean container, prepare a surfactant solution at a weight ratio of 0.3% to 0.5% of surfactant to water, ensuring that the solution is uniform and free of precipitation;

[0028] S2. Aggregate soaking:

[0029] Adding the functionalized lightweight aggregate into the surfactant solution, the liquid surface should cover the functionalized lightweight aggregate, and the weight ratio of the functionalized lightweight aggregate to the solution is 1:1.5;

[0030] Allow to soak for 10 minutes so that the surface of the functionalized lightweight aggregate can fully absorb the active molecules;

[0031] S3, ultrasonic dispersion:

[0032] The aggregate after the immersion treatment in step S2 is treated using an ultrasonic disperser, with the power set to 200 W and the frequency set to 40 kHz; the treatment time is 10 minutes;

[0033] S4. Drying:

[0034] Allow the treated aggregate to dry at room temperature to avoid excessive moisture residue affecting subsequent batching;

[0035] S5. Screening and activation of regenerated micro powder:

[0036] Use a 100-mesh sieve to sieve the regenerated micro powder and remove coarse particles to ensure that the particle size distribution is within the range of 10 to 30 microns;

[0037] The screened regenerated micro powder is placed in a ball mill, and Ca(OH)2 solution or Na2SiO3 solution is added at a weight ratio of 5% to 10% of the regenerated micro powder for 30 minutes to enhance its surface activity and reaction ability with cement;

[0038] The regenerated micro powder after ball milling and activation is placed in a dry sealed container for later use;

[0039] S6. Screening of self-healing microcapsule materials:

[0040] Use a sieve with a pore size of 50 to 150 microns to grade and screen the self-healing microcapsule material;

[0041] S7, initial low speed stirring and mixing:

[0042] Add cement, modified mineral admixture and activated recycled micro powder into the mixer in sequence;

[0043] Adding an initial amount of water of 6% to 8.75% of the weight of cement, stirring evenly to ensure that the slurry is moist but not diluted to obtain a premixed slurry;

[0044] S8. Adding aggregate and functional materials:

[0045] Adding polypropylene fibers, self-healing microcapsule materials after graded screening, and functionalized lightweight aggregates obtained by the S4 step into the premixed slurry;

[0046] S9, consistency adjustment and homogenization:

[0047] Add the remaining water and water reducing agent in batches;

[0048] The remaining water is added in batches, and the amount of the remaining water added is 50% of the target total water amount, and is added gradually in 3 to 4 times. If it is added in 3 times, each time is about 5.4% to 7.33% of the total slurry weight;

[0049] If added in 4 times, each time is about 4.05% to 5.5% of the total slurry weight;

[0050] Each time water is added, stir for 1 minute, observe the uniformity and consistency of the slurry, and make adjustments gradually to avoid slurry dilution or stratification;

[0051] The amount of water reducer added is 0.3% to 0.5% of the total cement weight, which can be added in batches after mixing with water when adding water for the first time;

[0052] Among them, stir for 1 minute after adding water and water reducing agent each time to ensure that the slurry is evenly distributed;

[0053] After completing the addition of the remaining water and water reducing agent, conduct a consistency test and measure whether the slump meets the target. If the consistency does not meet the target, increase or decrease by no more than 5% of the target total water volume.

[0054] Optionally, the method for preparing green lightweight wet-mix mortar further includes: in step S9, setting the target slump to 160-180 mm.

[0055] Optionally, the method for preparing the green lightweight wet-mixed mortar further comprises:

[0056] In step S7, the stirrer is set to a stirring speed of 50 rpm and the stirring is continued for 3 minutes.

[0057] Optionally, the method for preparing the green lightweight wet-mixed mortar further comprises:

[0058] In step S8, the stirring speed of the stirrer is adjusted to a stirring speed of 100 rpm, and the stirring time is 5 minutes.

[0059] Optionally, the method for preparing the green lightweight wet-mixed mortar further comprises:

[0060] In step S9, the stirring speed of the stirrer is adjusted to 200 rpm, and the stirring is continued for 2 minutes. During this process, it is ensured that the slurry is completely homogenized without segregation or water seepage.

[0061] Optionally, the method for preparing the green lightweight wet-mixed mortar further comprises:

[0062] The prepared wet-mixed mortar is placed in a sealed container with a capacity of 25 to 50 kg and stored at a room temperature of 20 to 30°C.

[0063] The beneficial effects achieved by the present invention are:

[0064] 1. The green lightweight wet-mix mortar has greatly improved its compressive strength through the active filling of recycled micropowder and the optimization of functional lightweight aggregates, meeting the needs of high-strength building applications. The introduction of self-healing microcapsule materials and polypropylene fibers has significantly improved the mortar's crack resistance and flexural resistance, making it suitable for crack-sensitive walls and decoration projects.

[0065] 2. Green lightweight wet-mix mortar uses functional lightweight aggregates to reduce the overall thermal conductivity of the mortar, has good thermal insulation effect, helps reduce building energy consumption, and meets the requirements of green energy-saving buildings.

[0066] 3. Green lightweight wet-mix mortar uses recycled micropowder made from waste concrete or waste bricks to replace part of the cement, which not only reduces dependence on natural resources, but also improves the comprehensive utilization rate of solid waste and reduces environmental pollution.

[0067] 4. Green lightweight wet-mix mortar is not prone to stratification and segregation during construction through precise water-cement ratio control and water-reducing agent optimization, and is suitable for mechanized spraying and traditional plastering.

[0068] 5. Green lightweight wet-mix mortar modified lightweight aggregate and recycled micropowder optimize the mortar pore structure, significantly reduce water absorption, enhance anti-seepage performance, and extend the service life of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0069] The present invention can be further understood from the following description in conjunction with the accompanying drawings. The components in the figures are not necessarily drawn to scale, but the emphasis is placed on illustrating the principles of the embodiments. In different views, the same reference numerals designate the same parts.

[0070] Figure 1 It is a schematic diagram of the compressive strength comparison effect of the present invention.

[0071] Figure 2 It is a schematic diagram of the comparative effect of the flexural strength of the present invention.

[0072] Figure 3 It is a schematic diagram of the comparative effect of water absorption of the present invention.

[0073] Figure 4 It is a schematic diagram of the comparative effect of thermal conductivity of the present invention.

[0074] Figure 5 It is a schematic diagram of the comparative effect of TVOC release of the present invention.

[0075] Figure 6 It is a schematic diagram of the comparative effect of formaldehyde emission of the present invention.

[0076] Figure 7 It is a schematic diagram of the comparison effect of comprehensive utilization rate of solid wastes of the present invention. DETAILED DESCRIPTION

[0077] The following is an explanation of the embodiments of the present invention through specific embodiments. Those skilled in the art can understand the advantages and effects of the present invention from the contents disclosed in this specification. The present invention can be implemented or applied through other different specific embodiments, and the details in this specification can also be modified and changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention. In addition, the drawings of the present invention are only simple schematic illustrations and are not depicted according to actual sizes. It is stated in advance. The following embodiments will further explain the relevant technical contents of the present invention in detail, but the disclosed contents are not intended to limit the scope of protection of the present invention.

[0078] Embodiment 1: A green lightweight wet-mixed mortar, the green lightweight wet-mixed mortar comprising the following components in weight percentage:

[0079] Cement: 30%;

[0080] Functionalized lightweight aggregate: 25%;

[0081] Recycled micro powder: 10%;

[0082] Self-healing microcapsule material: 0.7%;

[0083] Polypropylene fiber: 0.5%;

[0084] Modified mineral admixture: 6%;

[0085] Surfactant: 0.3%;

[0086] Water reducing agent: 0.5%;

[0087] Water: 27%.

[0088] The regenerated micro powder is obtained by crushing, screening and grinding waste concrete and waste bricks to obtain fine powder with an average particle size controlled between 10 and 30 microns.

[0089] Optionally, the self-healing microcapsule material includes a shell layer and a core layer, the shell layer material is made of a high molecular polymer (such as polyurethane, polyacrylate or epoxy resin), and the core layer is calcium silicate slurry (CaO-SiO2-H2O) or epoxy resin.

[0090] Optionally, the functionalized lightweight aggregate includes surface-modified expanded perlite or floating beads.

[0091] Optionally, the modified mineral admixture includes silica fume or fly ash.

[0092] In the present invention, the method for modifying the mineral admixture may be:

[0093] 1) Physical modification: Ultrafine grinding of fly ash or silica fume can make the particle size more uniform, increase the specific surface area, and improve its filling effect and activity in mortar.

[0094] Add surfactants or dispersants to reduce particle agglomeration and enhance uniform mixing with other components.

[0095] 2) Chemical modification: Use alkaline solution (such as Ca(OH)2, Na2SiO3) to activate fly ash or silica ash to form an active layer (such as calcium silicate layer) on its surface to improve its reactivity with cement.

[0096] Functional additives (such as silane coupling agents) can also be introduced to further improve the interfacial bonding properties between the admixture and the mortar matrix.

[0097] 3) Composite modification: Combining physical and chemical methods, such as first reducing the particle size through ultrafine grinding and then further activating it through alkaline solution, to achieve the best performance improvement effect.

[0098] Therefore, in this embodiment, the modified mineral admixture specifically refers to silica fume or fly ash formed by modification. That is, the modified mineral admixture specifically refers to fly ash, silica fume or slag powder modified by physical and / or chemical methods, which significantly improves the mechanical properties, durability and workability of green lightweight wet-mixed mortar by enhancing activity, optimizing particle size and interface performance, while reducing environmental impact.

[0099] In the present invention, the functionalized lightweight aggregate is based on expanded perlite or floating beads as a base material. The base material has light and porous properties. In this embodiment, its performance in wet mortar is improved by surface modification. The specific production steps of the functionalized lightweight aggregate of the present invention include:

[0100] ① Preparation of surfactant solution: In a clean container, the surfactant solution is mixed at a ratio of 0.3% to 0.5% by weight of water for surface modification of lightweight aggregate.

[0101] Stir well to ensure that the solution is free of precipitation.

[0102] ② Soaking treatment: Add lightweight aggregate (such as expanded perlite or floating beads) into the surfactant solution. The liquid surface should cover the aggregate. Add the aggregate and solution at a weight ratio of 1:1.5. Soak for 10 minutes to allow the surface of the lightweight aggregate to fully absorb the active molecules and improve its bonding performance with the mortar matrix.

[0103] ③Ultrasonic dispersion treatment: Use ultrasonic disperser to treat the aggregate after soaking treatment:

[0104] Power: 200~400W;

[0105] Frequency: 20~40kHz;

[0106] Processing time: 10 minutes.

[0107] Ultrasonic action can enhance the uniform distribution of active molecules, remove loose particles from the aggregate surface, and form a uniform active coating.

[0108] ④ Drying treatment: Let the aggregate after ultrasonic dispersion stand at room temperature to dry to avoid excessive moisture residue. This step can ensure the stability of the aggregate in subsequent use.

[0109] ⑤ Chemical modification: To further enhance the chemical activity of the aggregate surface, the dried aggregate can be immersed in an alkaline solution (such as Ca(OH)2 or Na2SiO3 solution). An active layer (such as a calcium silicate layer) is formed on the aggregate surface through chemical reactions.

[0110] Soaking time: 5 to 10 minutes; solution concentration: 5% to 10%.

[0111] The aggregate is then removed and dried to form the functionalized lightweight aggregate.

[0112] The green lightweight wet-mix mortar preparation method comprises the following steps:

[0113] S1. Prepare surfactant solution:

[0114] In a clean container, prepare a surfactant solution at a weight ratio of 0.3% to 0.5% of surfactant to water, ensuring that the solution is uniform and free of precipitation;

[0115] S2. Aggregate soaking:

[0116] Adding the functionalized lightweight aggregate into the surfactant solution, the liquid surface should cover the functionalized lightweight aggregate, and the weight ratio of the functionalized lightweight aggregate to the solution is 1:1.5;

[0117] Allow to soak for 10 minutes so that the surface of the functionalized lightweight aggregate can fully absorb the active molecules;

[0118] S3, ultrasonic dispersion:

[0119] The aggregates soaked in step S2 were treated with an ultrasonic disperser, with the power set to 200 W and the frequency set to 40 kHz; the treatment time was 10 minutes. The high-frequency vibration and micro-jet action of the ultrasonic wave further dispersed the active molecules adsorbed on the surface of the aggregates, removed the loose particles on the surface of the aggregates, and ensured that a complete and uniform active coating was formed on the surface of the functionalized lightweight aggregates.

[0120] S4. Drying:

[0121] The treated functionalized lightweight aggregate is left to dry at room temperature;

[0122] S5. Screening and activation of regenerated micro powder:

[0123] The regenerated micro powder is screened with a 100-mesh screen to remove coarse particles to ensure that the particle size distribution is within the range of 10 to 30 microns; the screened regenerated micro powder is placed in a ball mill, and Ca(OH)2 solution or Na2SiO3 solution is added at a weight ratio of 5% to 10% of the regenerated micro powder, and the ball milling time is 30 minutes;

[0124] The regenerated micro powder after ball milling and activation is placed in a dry sealed container for later use;

[0125] The ball milling process reduces the particle size through mechanical action and activates the particle surface through chemical solution. The activated regenerated micro powder remains in a granular state and is placed in a dry and sealed container for later use.

[0126] S6. Screening of self-healing microcapsule materials:

[0127] Use a sieve with a pore size of 50 to 150 microns to grade and screen the self-healing microcapsule material;

[0128] S7, initial low speed stirring and mixing:

[0129] Add cement, modified mineral admixture and activated recycled micro powder in a mixer in sequence; stir evenly to ensure that the slurry is moist but not diluted to obtain a premixed slurry;

[0130] S8. Adding the functionalized lightweight aggregate and functional materials (polypropylene fiber and self-healing microcapsule material) obtained by the treatment in step S4:

[0131] Adding polypropylene fibers, self-healing microcapsule materials after graded screening, and functionalized lightweight aggregates obtained by the S4 step into the premixed slurry;

[0132] S9, consistency adjustment and homogenization:

[0133] Add the remaining water and water reducing agent in portions.

[0134] Each time water is added, stir for 1 minute, observe the uniformity and consistency of the slurry, and make adjustments gradually to avoid slurry dilution or stratification;

[0135] The water reducing agent added separately accounts for 0.5% of the total slurry weight. It can be mixed with water when adding water for the first time and then added in batches;

[0136] Among them, stir for 1 minute after adding water and water reducing agent each time to ensure that the slurry is evenly distributed;

[0137] After completing the addition of the remaining water and water reducing agent, conduct a consistency test and measure whether the slump meets the target. If the consistency does not meet the target, increase or decrease by no more than 5% of the target total water volume.

[0138] In this embodiment, recycled micropowder is used, and after screening and activation treatment, its particle size is optimized and its surface activity is enhanced, so it can form more CSH gel with the cement matrix, effectively improving the compressive strength of the mortar. Experiments show that the compressive strength of Example 1 reaches 12.5MPa, which is 13.6% higher than the ordinary mortar (11MPa) of the control example. At the same time, the synergistic effect of the self-healing microcapsule material and polypropylene fiber significantly enhances the flexural properties of the mortar, and the ability to resist cracks is stronger. The flexural strength reaches 3.8MPa, which is more than 20% higher than the control example. In addition, the use of recycled micropowder and modified mineral admixtures to replace part of the cement reduces the cost of raw materials. The lightweight design reduces transportation costs and building loads, and improves overall economy.

[0139] In summary, through scientific formula design and advanced preparation technology, significant beneficial effects have been shown in many aspects. By introducing modified mineral admixtures, functionalized lightweight aggregates and recycled micropowders, the mortar significantly improves its mechanical properties, durability and environmental performance, while reducing the dry density of the material and giving it lightweight characteristics. The activation treatment of recycled micropowders enhances the surface activity of its particles, forms more CSH gels with the cement matrix, greatly improves the compressive strength and flexural properties of the mortar, and improves the durability and crack resistance of the material. The use of functionalized lightweight aggregates effectively reduces the density of the mortar and optimizes the pore structure, significantly reduces its water absorption rate, and has excellent anti-permeability properties, making it suitable for harsh environments. The introduction of self-healing microcapsule materials enhances the material's crack resistance and further extends its service life. At the same time, the use of recycled micropowders made from waste concrete or waste bricks to replace part of the cement improves the comprehensive utilization rate of solid waste, effectively reduces the burden of construction waste on the environment, and reduces carbon emissions.

[0140] Embodiment 2: A green lightweight wet-mixed mortar, the green lightweight wet-mixed mortar comprising the following components in weight percentage:

[0141] Cement: 35%;

[0142] Functionalized lightweight aggregate: 25%;

[0143] Recycled micro powder: 10%;

[0144] Self-healing microcapsule material: 1.0%;

[0145] Polypropylene fiber: 0.7%;

[0146] Modified mineral admixture: 7%;

[0147] Surfactant: 0.3%;

[0148] Water reducing agent: 0.5%;

[0149] Water: 20.5%.

[0150] The green lightweight wet-mix mortar preparation method comprises the following steps:

[0151] S1. Prepare surfactant solution:

[0152] In a clean container, prepare a surfactant solution at a weight ratio of 0.3% to 0.5% of surfactant to water, ensuring that the solution is uniform and free of precipitation;

[0153] S2. Aggregate soaking:

[0154] Adding the functionalized lightweight aggregate into the surfactant solution, the liquid surface should cover the functionalized lightweight aggregate, and the weight ratio of the functionalized lightweight aggregate to the solution is 1:1.5;

[0155] Allow to soak for 10 minutes so that the surface of the functionalized lightweight aggregate can fully absorb the active molecules;

[0156] S3, ultrasonic dispersion:

[0157] The aggregates soaked in step S2 were treated with an ultrasonic disperser, with the power set to 200 W and the frequency set to 40 kHz; the treatment time was 10 minutes. The high-frequency vibration and micro-jet action of the ultrasonic wave further dispersed the active molecules adsorbed on the surface of the aggregates, removed the loose particles on the surface of the aggregates, and ensured that a complete and uniform active coating was formed on the surface of the functionalized lightweight aggregates.

[0158] S4. Drying:

[0159] The treated functionalized lightweight aggregate is left to dry at room temperature;

[0160] S5. Screening and activation of regenerated micro powder:

[0161] The regenerated micro powder is screened with a 100-mesh screen to remove coarse particles to ensure that the particle size distribution is within the range of 10 to 30 microns; the screened regenerated micro powder is placed in a ball mill, and Ca(OH)2 solution or Na2SiO3 solution is added at a weight ratio of 5% to 10% of the regenerated micro powder, and the ball milling time is 30 minutes;

[0162] The regenerated micro powder after ball milling and activation is placed in a dry sealed container for later use;

[0163] The ball milling process reduces the particle size through mechanical action and activates the particle surface through chemical solution. The activated regenerated micro powder remains in a granular state and is placed in a dry and sealed container for later use.

[0164] S6. Screening of self-healing microcapsule materials:

[0165] Use a sieve with a pore size of 50 to 150 microns to grade and screen the self-healing microcapsule material;

[0166] S7, initial low speed stirring and mixing:

[0167] Add cement, modified mineral admixture and activated recycled micro powder into the mixer in sequence; stir at low speed for 3 minutes to ensure that the slurry is moistened but not diluted to obtain a premixed slurry.

[0168] S8. Adding the functionalized lightweight aggregate and functional materials (polypropylene fiber and self-healing microcapsule material) obtained by the treatment in step S4:

[0169] Polypropylene fibers, self-healing microcapsule materials obtained after graded screening, and functionalized lightweight aggregates obtained through the S4 step are added to the premixed slurry.

[0170] S9, consistency adjustment and homogenization:

[0171] Add the remaining water and water reducing agent in batches;

[0172] Add the remaining water in batches, stir for 1 minute after each addition, observe the uniformity and consistency of the slurry, and make adjustments gradually to avoid dilution or stratification of the slurry.

[0173] The water reducer added separately, the water reducer accounts for 0.5% of the total slurry weight, and can be mixed with water when adding water for the first time and then added in batches;

[0174] Among them, stir for 1 minute after adding water and water reducing agent each time to ensure that the slurry is evenly distributed;

[0175] After completing the addition of the remaining water and water reducing agent, conduct a consistency test and measure whether the slump meets the target. If the consistency does not meet the target, increase or decrease by no more than 5% of the target total water volume.

[0176] Embodiment 3: A green lightweight wet-mixed mortar, the green lightweight wet-mixed mortar comprising the following components in weight percentage:

[0177] Cement: 32%;

[0178] Functionalized lightweight aggregate: 25%;

[0179] Recycled micro powder: 10%;

[0180] Self-healing microcapsule material: 1.0%;

[0181] Polypropylene fiber: 0.7%;

[0182] Modified mineral admixture: 7%;

[0183] Surfactant: 0.3%;

[0184] Water reducing agent: 0.5%;

[0185] Water: 23.5%.

[0186] The green lightweight wet-mix mortar preparation method comprises the following steps:

[0187] S1. Prepare surfactant solution:

[0188] In a clean container, prepare a surfactant solution at a weight ratio of 0.3% to 0.5% of surfactant to water, ensuring that the solution is uniform and free of precipitation;

[0189] S2. Aggregate soaking:

[0190] Adding the functionalized lightweight aggregate into the surfactant solution, the liquid surface should cover the functionalized lightweight aggregate, and the weight ratio of the functionalized lightweight aggregate to the solution is 1:1.5;

[0191] Allow to soak for 10 minutes so that the surface of the functionalized lightweight aggregate can fully absorb the active molecules;

[0192] S3, ultrasonic dispersion:

[0193] The aggregates soaked in step S2 were treated with an ultrasonic disperser, with the power set to 200 W and the frequency set to 40 kHz; the treatment time was 10 minutes. The high-frequency vibration and micro-jet action of the ultrasonic wave further dispersed the active molecules adsorbed on the surface of the aggregates, removed the loose particles on the surface of the aggregates, and ensured that a complete and uniform active coating was formed on the surface of the functionalized lightweight aggregates.

[0194] S4. Drying:

[0195] The treated functionalized lightweight aggregate is left to dry at room temperature;

[0196] S5. Screening and activation of regenerated micro powder:

[0197] The regenerated micro powder is screened with a 100-mesh screen to remove coarse particles to ensure that the particle size distribution is within the range of 10 to 30 microns; the screened regenerated micro powder is placed in a ball mill, and Ca(OH)2 solution or Na2SiO3 solution is added at a weight ratio of 5% to 10% of the regenerated micro powder, and the ball milling time is 30 minutes;

[0198] The regenerated micro powder after ball milling and activation is placed in a dry sealed container for later use;

[0199] S6. Screening of self-healing microcapsule materials:

[0200] Use a sieve with a pore size of 50 to 150 microns to grade and screen the self-healing microcapsule material;

[0201] S7, initial low speed stirring and mixing:

[0202] Adding cement, modified mineral admixture and activated recycled micro powder in a mixer in sequence to obtain a premixed slurry;

[0203] S8. Add the functionalized lightweight aggregate and functional material obtained by the treatment in step S4:

[0204] Adding polypropylene fibers, self-healing microcapsule materials after graded screening, and functionalized lightweight aggregates obtained by the S4 step into the premixed slurry;

[0205] S9, consistency adjustment and homogenization:

[0206] Add the remaining water and water reducing agent in batches;

[0207] The remaining water was added in portions.

[0208] Each time water is added, stir for 1 minute, observe the uniformity and consistency of the slurry, and make adjustments gradually to avoid slurry dilution or stratification;

[0209] The total amount of water reducing agent added separately is 0.5% of the total slurry weight, which can be added in batches after mixing with water when adding water for the first time;

[0210] Among them, stir for 1 minute after adding water and water reducing agent each time to ensure that the slurry is evenly distributed;

[0211] After completing the addition of the remaining water and water reducing agent, conduct a consistency test and measure whether the slump meets the target. If the consistency does not meet the target, increase or decrease by no more than 5% of the target total water volume.

[0212] Embodiment 4: A green lightweight wet-mixed mortar, the green lightweight wet-mixed mortar comprising the following components in weight percentage:

[0213] Cement: 34.8%;

[0214] Functionalized lightweight aggregate: 25%;

[0215] Recycled micro powder: 12%;

[0216] Self-healing microcapsule material: 0.5%;

[0217] Polypropylene fiber: 0.7%;

[0218] Modified mineral admixture: 7%;

[0219] Surfactant: 0.3%;

[0220] Water reducing agent: 0.5%;

[0221] Water: 19.2%.

[0222] The green lightweight wet-mix mortar preparation method comprises the following steps:

[0223] S1. Prepare surfactant solution:

[0224] In a clean container, prepare a surfactant solution at a weight ratio of 0.3% to 0.5% of surfactant to water, ensuring that the solution is uniform and free of precipitation;

[0225] S2. Aggregate soaking:

[0226] Adding the functionalized lightweight aggregate into the surfactant solution, the liquid surface should cover the functionalized lightweight aggregate, and the weight ratio of the functionalized lightweight aggregate to the solution is 1:1.5;

[0227] Allow to soak for 10 minutes so that the surface of the functionalized lightweight aggregate can fully absorb the active molecules;

[0228] S3, ultrasonic dispersion:

[0229] The aggregates soaked in step S2 were treated with an ultrasonic disperser, with the power set to 200 W and the frequency set to 40 kHz; the treatment time was 10 minutes. The high-frequency vibration and micro-jet action of the ultrasonic wave further dispersed the active molecules adsorbed on the surface of the aggregates, removed the loose particles on the surface of the aggregates, and ensured that a complete and uniform active coating was formed on the surface of the functionalized lightweight aggregates.

[0230] S4. Drying:

[0231] The treated functionalized lightweight aggregate is left to dry at room temperature;

[0232] S5. Screening and activation of regenerated micro powder:

[0233] The regenerated micro powder is screened with a 100-mesh screen to remove coarse particles to ensure that the particle size distribution is within the range of 10 to 30 microns; the screened regenerated micro powder is placed in a ball mill, and Ca(OH)2 solution or Na2SiO3 solution is added at a weight ratio of 5% to 10% of the regenerated micro powder, and the ball milling time is 30 minutes;

[0234] The regenerated micro powder after ball milling and activation is placed in a dry sealed container for later use;

[0235] S6. Screening of self-healing microcapsule materials:

[0236] Use a sieve with a pore size of 50 to 150 microns to grade and screen the self-healing microcapsule material;

[0237] S7, initial low speed stirring and mixing:

[0238] Add cement, modified mineral admixture, recycled micro powder and initial water into the mixer in sequence; stir at low speed for 3 minutes to ensure that the slurry is moist but not diluted, so as to obtain a premixed slurry.

[0239] S8. Adding the functionalized lightweight aggregate and functional materials (polypropylene fiber and self-healing microcapsule material) obtained by the treatment in step S4:

[0240] Polypropylene fibers, self-healing microcapsule materials obtained after graded screening, and functionalized lightweight aggregates obtained through the S4 step are added to the premixed slurry.

[0241] S9, consistency adjustment and homogenization:

[0242] Add the remaining water and water reducing agent in batches;

[0243] The remaining water was added in portions.

[0244] Each time water is added, stir for 1 minute, observe the uniformity and consistency of the slurry, and make adjustments gradually to avoid slurry dilution or stratification;

[0245] The water reducer added separately can be mixed with water when adding water for the first time and then added in batches;

[0246] Among them, stir for 1 minute after adding water and water reducing agent each time to ensure that the slurry is evenly distributed;

[0247] After completing the addition of the remaining water and water reducing agent, conduct a consistency test and measure whether the slump meets the target. If the consistency does not meet the target, increase or decrease by no more than 5% of the target total water volume.

[0248] Comparative Example 1: A green lightweight wet-mixed mortar, the green lightweight wet-mixed mortar comprising the following components in weight percentage:

[0249] Cement: 40%;

[0250] Ordinary lightweight aggregate (unmodified expanded perlite): 30%;

[0251] Ordinary fine sand: 20%;

[0252] Polypropylene fiber: 0.5%;

[0253] Modified mineral admixture (fly ash): 8%;

[0254] Surfactant: 0.3%;

[0255] Water reducing agent: 0.4%;

[0256] Water: 0.8%;

[0257] The method for preparing the green lightweight wet-mixed mortar of Comparative Example 1 comprises the following steps:

[0258] SD11, Raw material preparation:

[0259] Prepare surfactant solution: In a clean container, prepare surfactant solution according to the weight ratio of surfactant to water of 0.3% to 0.5% (0.3% in this example), stir evenly to ensure no precipitation.

[0260] Ordinary lightweight aggregate and ordinary fine sand can be used directly without special treatment.

[0261] SD12, initial low speed stirring:

[0262] Cement (40%), ordinary fine sand (20%), modified mineral admixture (8%) and initial water were added into the mixer in sequence.

[0263] Initial water volume: 9.0% of the total slurry weight, stir at low speed for 3 minutes to ensure that the slurry is moist but not diluted.

[0264] In this embodiment, during the low-speed stirring stage, the rotation speed of the stirrer is set to 60 to 100 rpm.

[0265] SD13, medium speed stirring:

[0266] Ordinary lightweight aggregate (30%), polypropylene fiber (0.5%) and surfactant solution (0.3%) were added.

[0267] Mix at medium speed for 5 minutes to ensure even distribution of the slurry and avoid aggregate agglomeration.

[0268] In this embodiment, in the medium-speed stirring stage, the rotation speed of the stirrer is set to 150-200 rpm.

[0269] SD14, consistency adjustment and homogenization:

[0270] Add the remaining water in batches. The remaining water added is 12.8% of the total slurry weight. Add gradually in 3 to 4 batches:

[0271] If added in 3 times, the amount of water added each time is 33.3% (about 4.27%) of the remaining water;

[0272] If the water is added in 4 times, the amount of water added each time is 25% (about 3.2%) of the remaining water. After each addition of water, stir for 1 minute and observe the consistency and uniformity of the slurry.

[0273] Add water reducer (0.4% by weight of total slurry) in portions and stir for 1 minute to ensure even distribution.

[0274] SD15, consistency test:

[0275] Consistency test: After completing the addition of the remaining water and water reducing agent, conduct a consistency test and measure the slump to ensure that the slump is within the target range.

[0276] If the consistency does not meet the target (too high or too low), adjust the water volume (increase or decrease should not exceed 0.04% of the total water volume).

[0277] Comparative Example 2: A green lightweight wet-mixed mortar, the green lightweight wet-mixed mortar comprising the following components in weight percentage:

[0278] Cement: 35%;

[0279] Ordinary lightweight aggregate (unmodified expanded perlite): 25%;

[0280] Ordinary fine sand: 25%;

[0281] Polypropylene fiber: 0.7%;

[0282] Modified mineral admixture (fly ash): 7%;

[0283] Surfactant: 0.4%;

[0284] Water reducing agent: 0.5%;

[0285] Water: 6.4%;

[0286] The method for preparing the green lightweight wet-mixed mortar of Comparative Example 2 comprises the following steps:

[0287] SD21. Raw material preparation: Prepare surfactant solution:

[0288] In a clean container, prepare a surfactant solution according to a weight ratio of surfactant to water of 0.3% to 0.5% (0.4% in this example), stir evenly to ensure no precipitation.

[0289] Ordinary lightweight aggregate and ordinary fine sand: can be used directly without special treatment.

[0290] SD22, initial low speed stirring:

[0291] Cement (35%);

[0292] Ordinary fine sand (25%);

[0293] Modified mineral admixture (7%);

[0294] The initial amount of water added was 1.34% of the total slurry weight, and stirred at a low speed for 3 minutes to ensure that the slurry was moist but not diluted.

[0295] In this embodiment, during the low-speed stirring stage, the speed of the stirrer is set at 60 to 100 rpm. SD23, medium-speed stirring, add:

[0296] Ordinary lightweight aggregate (25%);

[0297] Polypropylene fiber (0.7%);

[0298] Surfactant solution (0.4%).

[0299] Mix at medium speed for 5 minutes to ensure even distribution of the slurry and avoid aggregate agglomeration.

[0300] In this embodiment, during the medium-speed stirring stage, the speed of the stirrer is set to 150-200 rpm. SD24, consistency adjustment and homogenization:

[0301] Add the remaining water in batches. The remaining water added is 5.06% of the total slurry weight. Add gradually in 3 to 4 batches:

[0302] If added in 3 times, the amount of water added each time is 33.3% (about 1.69%) of the remaining water;

[0303] If adding in 4 times, the amount of water added each time is 25% (about 1.27%) of the remaining water.

[0304] After each addition of water, stir for 1 minute and observe the consistency and uniformity of the slurry.

[0305] SD25, consistency test: After completing the addition of the remaining water and water reducing agent, conduct a consistency test and measure the slump to ensure that it meets the target (moderate consistency and slump within a reasonable range).

[0306] If the consistency does not meet the target (too high or too low), adjust the water volume (increase or decrease should not exceed 0.32% of the total water volume).

[0307] Comparative Example 3: Ordinary mortar.

[0308] In this application, all examples and comparative examples are based on a total slurry weight of 100 kg. This setting is in line with the specification, helps to compare and analyze the performance differences of different formulations, and is convenient for expansion to other scale production. If the benchmark needs to be changed, it can be directly scaled up or down according to the ratio.

[0309] Green lightweight wet-mix mortar has greatly improved its compressive strength through the active filling of recycled micropowder and the optimization of functional lightweight aggregates, meeting the needs of high-strength building applications. The introduction of self-healing microcapsule materials and polypropylene fibers has significantly improved the mortar's crack resistance and flexural resistance, making it suitable for crack-sensitive walls and decoration projects.

[0310] Green lightweight wet-mix mortar uses functional lightweight aggregates to reduce the overall thermal conductivity of the mortar, has good thermal insulation effects, helps reduce building energy consumption, and meets the requirements of green energy-saving buildings.

[0311] Referring to the "Test Method for Cement Mortar Strength", the size of the test block is 45mm×40mm×180mm. The mortar is mixed in a mixer and then formed in a mortar mold. It is demoulded after curing in a standard curing box for 24 hours, and then cured for 28 days at 20±3℃, relative humidity>95% and 55℃, relative humidity>95%. The compressive strength and flexural strength are tested by a servo universal testing machine and recorded in Table 1 below.

[0312] The water absorption of green lightweight wet-mixed mortar was measured with reference to GB / T 12960-2007 "Test methods for building waterproof materials" and recorded in Table 1. The thermal conductivity of green lightweight wet-mixed mortar was measured with reference to GB / T10294-2008 "Determination of steady-state thermal resistance and related properties of insulation materials" and recorded in Table 1.

[0313] The release of harmful substances from green lightweight wet-mixed mortar was measured with reference to GB / T 37884-2019 "Determination of VOC emission" and recorded in Table 1 below.

[0314] Table 1 Performance test results

[0315]

[0316] From Table 1 and Figure 1 It can be seen from the data that the compressive strength of Examples 1 to 4 of the present invention is significantly higher than that of Comparative Examples 1 and 2. The compressive strength of Example 4 is the highest, which is 16.2 MPa, which is about 47.3% higher than the 11.0 MPa of Comparative Example 3 (ordinary mortar). From the comparison between Example 2 and Comparative Example 1, it can be seen that the active filling effect of the regenerated micropowder improves the compressive strength, while Comparative Example 1 does not use regenerated micropowder, and its compressive strength is only 8.7 MPa. From the comparison between Example 3 and Comparative Example 2, it can be seen that the self-healing microcapsule material and polypropylene fiber have a positive effect on the repair and crack resistance of cracks, and significantly improve the compressive strength (10.8 MPa vs. 9.3 MPa).

[0317] From Table 1 and Figure 2 It can be seen from the data that the flexural strength of Examples 1 to 4 ranges from 3.2 to 4.8 MPa, which is significantly better than Comparative Examples 1 and 2 (2.5 to 2.8 MPa). From the comparison between Example 4 and Comparative Example 3, it can be seen that the synergistic effect of the fiber and the regenerated micropowder in the present invention effectively improves the flexural performance of the mortar and enhances the toughness (4.8 MPa vs. 3.0 MPa, an increase of 60%).

[0318] From Table 1 and Figure 3 It can be seen from the data that the water absorption rates of Examples 1 to 4 are between 9.5% and 11.2%, which are significantly lower than those of the comparative examples (14.5% to 16.8%). From the comparison between Example 2 and Comparative Example 1, it can be seen that the use of modified lightweight aggregate effectively reduces the water absorption rate (9.8% vs. 15.0%), improves the anti-seepage performance, and is suitable for high humidity environments. From the comparison between Example 3 and Comparative Example 2, it can be seen that the use of self-healing microcapsule materials has a significant effect on reducing the water absorption rate, reducing the water absorption rate from 14.5% to 11.2%, showing better durability.

[0319] From Table 1 and Figure 4 It can be seen from the data that the thermal conductivity of Examples 1 to 4 ranges from 0.18 to 0.22 W / m·K, which is much lower than that of the comparative example (0.32 to 0.50 W / m·K). From the comparison between Example 3 and Comparative Example 3, it can be seen that the synergistic effect of the recycled micropowder and the lightweight aggregate significantly reduces the thermal conductivity (0.18 W / m·K vs. 0.50 W / m·K, a decrease of 64%), reflecting the excellent thermal insulation effect. From the comparison between Example 2 and Comparative Example 1, it can be seen that the ordinary lightweight aggregate of Comparative Example 1 has not been modified and has a thermal conductivity of 0.35 W / m·K, while the modified lightweight aggregate of Example 2 reduces the thermal conductivity to 0.20 W / m·K, and has better thermal insulation performance.

[0320] From Table 1 and Figure 5 , Figure 6 It can be seen from the data that the TVOC emission and formaldehyde emission of Examples 1 to 4 are all controlled at 0.2 to 0.4 mg / m 3 between 1.2 and 1.8 mg / m 3 ). From the comparison between Example 4 and Comparative Example 3, it can be seen that the green lightweight mortar significantly reduces the release of harmful substances (reduced by about 88%) by using environmentally friendly raw materials and controlling the source of solid waste.

[0321] From Table 1 and Figure 7 It can be seen from the data that the comprehensive utilization rate of solid waste in Examples 1 to 4 ranges from 30% to 45%, while that in the comparative examples is 0%. From the comparison between Example 4 and Comparative Example 1, it can be seen that the use of recycled micropowder greatly improves the resource utilization rate, highlighting the characteristics of green environmental protection. From the comparison between Example 3 and Comparative Example 2, it can be seen that by reasonably proportioning recycled materials, Example 3 can still achieve a solid waste utilization rate of 30%, while Comparative Example 2 does not use recycled materials at all.

[0322] By replacing part of the cement with green lightweight wet-mix mortar and optimizing the production process, carbon dioxide emissions and energy consumption are greatly reduced, meeting the low-carbon and environmental protection requirements of green building materials. At the same time, the material density is significantly reduced, the building load is reduced, which is beneficial to high-rise buildings and energy-saving renovation projects.

[0323] Green lightweight wet-mix mortar uses recycled micropowder made from waste concrete or waste bricks to replace part of the cement, which not only reduces dependence on natural resources, but also improves the comprehensive utilization rate of solid waste and reduces environmental pollution.

[0324] Green lightweight wet-mix mortar is not prone to stratification and segregation during construction through precise water-cement ratio control and water-reducing agent optimization, and is suitable for mechanized spraying and traditional plastering.

[0325] Green lightweight wet-mix mortar modified lightweight aggregate and recycled micropowder optimize the mortar pore structure, significantly reduce water absorption, enhance anti-seepage performance and extend the service life of the material.

[0326] The contents disclosed above are only preferred feasible embodiments of the present invention, and do not limit the protection scope of the present invention. Therefore, all equivalent technical changes made using the contents of the present invention specification and drawings are included in the protection scope of the present invention. In addition, the elements therein can be updated as technology develops.

Claims

1. A green lightweight wet-mix mortar, characterized in that: The green lightweight wet-mixed mortar comprises the following components in weight percentage: Cement: 30%-35%; Functionalized lightweight aggregate: 20% to 26%; Recycled micro powder: 10% to 12%; Self-healing microcapsule material: 0.5%~1.0%; Polypropylene fiber: 0.5% to 0.7%; Modified mineral admixture: 5% to 8%; Surfactant: 0.2% to 0.4%; Water reducing agent: 0.3%~0.5%; Water: 16.3%~27%; The regenerated micro powder is obtained by crushing, screening and grinding waste concrete and waste bricks to obtain fine powder with an average particle size controlled between 10 and 30 microns.

2. The green lightweight wet-mix mortar according to claim 1, characterized in that: The self-healing microcapsule material comprises a shell layer and a core layer. The shell layer material is made of a high molecular polymer, and the core layer is calcium silicate slurry or epoxy resin.

3. The green lightweight wet-mix mortar according to claim 2, characterized in that: The functionalized lightweight aggregate includes surface-modified expanded perlite or floating pearls.

4. The green lightweight wet-mix mortar according to claim 3, characterized in that: The modified mineral admixture includes silica fume or fly ash.

5. A method for preparing green lightweight wet-mixed mortar, applied to the green lightweight wet-mixed mortar according to claim 3, characterized in that: The green lightweight wet-mix mortar preparation method comprises the following steps: S1. Prepare surfactant solution: In a clean container, prepare a surfactant solution at a weight ratio of 0.3% to 0.5% of surfactant to water, ensuring that the solution is uniform and free of precipitation; S2. Aggregate soaking: Adding the functionalized lightweight aggregate into the surfactant solution, the liquid surface should cover the functionalized lightweight aggregate, and the weight ratio of the functionalized lightweight aggregate to the solution is 1:1.5; Allow to soak for 10 minutes so that the surface of the functionalized lightweight aggregate can fully absorb the active molecules; S3, ultrasonic dispersion: The aggregate after the immersion treatment in step S2 is treated using an ultrasonic disperser, with the power set to 200 W and the frequency set to 40 kHz; the treatment time is 10 minutes; S4. Drying: The treated functionalized lightweight aggregate is left to dry at room temperature; S5. Screening and activation of regenerated micro powder: The regenerated micro powder is screened with a 100-mesh screen to remove coarse particles to ensure that the particle size distribution is within the range of 10-30 microns; the screened regenerated micro powder is placed in a ball mill, and Ca(OH)2 solution or Na2SiO3 solution is added at a weight ratio of 5% to 10% of the regenerated micro powder, and the ball milling time is 30 minutes; The regenerated micro powder after ball milling and activation is placed in a dry sealed container for later use; S6. Screening of self-healing microcapsule materials: Use a sieve with a pore size of 50 to 150 microns to grade and screen the self-healing microcapsule material; S7, initial low speed stirring and mixing: Add cement, modified mineral admixture and activated recycled micro powder into the mixer in sequence; Add the initial amount of water and stir evenly to ensure that the slurry is moistened but not diluted to obtain a premixed slurry; S8. Adding aggregate and functional materials: Adding polypropylene fibers, self-healing microcapsule materials after graded screening, and functionalized lightweight aggregates obtained by the S4 step into the premixed slurry; S9, consistency adjustment and homogenization: Add the remaining water and water reducing agent in batches; The remaining water was added in 3 to 4 portions, and the mixture was stirred for 1 minute after each addition of water. The uniformity and consistency of the slurry were observed and adjusted gradually to avoid dilution or stratification of the slurry. The amount of water reducer added is 0.3% to 0.5% of the total cement weight, which should be added in batches after mixing with water when adding water for the first time; Among them, stir for 1 minute after adding water and water reducing agent each time to ensure that the slurry is evenly distributed; After completing the addition of the remaining water and water reducing agent, conduct a consistency test and measure whether the slump meets the target. If the consistency does not meet the target, increase or decrease by no more than 5% of the target total water volume.

6. The method for preparing green lightweight wet-mix mortar according to claim 5, characterized in that: The method for preparing green lightweight wet-mix mortar also includes: in step S9, setting the target slump to 160-180 mm.

7. The method for preparing green lightweight wet-mixed mortar according to claim 6, characterized in that: The green lightweight wet-mixed mortar preparation method also includes: In step S7, the stirrer is set to a stirring speed of 50 rpm and the stirring is continued for 3 minutes.

8. The method for preparing green lightweight wet-mixed mortar according to claim 7, characterized in that: The green lightweight wet-mixed mortar preparation method also includes: In step S8, the stirring speed of the stirrer is adjusted to a stirring speed of 100 rpm, and the stirring time is 5 minutes.

9. The method for preparing green lightweight wet-mix mortar according to claim 8, characterized in that: The green lightweight wet-mixed mortar preparation method also includes: In step S9, the stirring speed of the stirrer is adjusted to 200 rpm, and the stirring is continued for 2 minutes. During this process, it is ensured that the slurry is completely homogenized without segregation or water seepage.

10. The method for preparing green lightweight wet-mixed mortar according to claim 9, characterized in that: The green lightweight wet-mixed mortar preparation method also includes: The prepared wet-mixed mortar is placed in a sealed container with a capacity of 25 to 50 kg and stored at a room temperature of 20 to 30°C.

Citation Information

Patent Citations

  • A lightweight plastering mortar based on anhydrite and its preparation method

    CN111410502B